A window into magnetic reconnection: IRIS observations of the consequences of reconnection during solar flares - Reeves, Katharine K. (Frontiers in Astronomy and Space Sciences, 2022)
Magnetic reconnection is a dynamic process that occurs in solar flares in a tenuous and hot environment. High-cadence, high-spatial resolution spectroscopic observations with the Interface Region Imaging Spectrometer (IRIS) have provided a unique window into the reconnection process that occurs during solar flares. IRIS has observed many consequences of the reconnection process, including detailed observations of outflows that are thought to be indicative of reconnection, possible observations of the termination shocks that are predicted by-products of reconnection, and observations of flare ribbons which are imprints of the reconnection process in the chromosphere. This paper will review these observations and put them in the context of flare models that predict reconnection signatures.